A novel extraction method enhanced the osteogenic and anti-osteoporosis effect of tea extract without any hepatotoxicity in ovariectomized rats - Kulkarni, Chirag; Sharma, Shivani; Bora, Prateek Singh; Verma, Saurabh; Rajput, Swati; Porwal, Konica; Rath, Srikanta Kumar; Gayen, Jiaur Rahaman; Sharma, Upendra; Chattopadhyay, Naibedya (Frontiers in Endocrinology, 2022)
Tea (Camellia sinensis) has several reported health benefits including that on bone health attributed to catechins of which the most abundant is epigallocatechin-3-gallate (EGCG). However, several preclinical and clinical studies have raised safety concerns of EGCG in tea extract to cause acute liver failure. Tea also contains kaempferol albeit scanty and it has hepatoprotective and osteogenic effects. Here, we utilised a novel extraction procedure of acid hydrolysis to enhance the osteogenic effect of tea extract while reducing its hepatotoxicity. The resultant extract (USKECSE) have a 40-fold increase in kaempferol and 2.5-fold reduction in EGCG contents compared with the hydroethanolic extract (USCSE). In a female Sprague Dawley (SD) rat femur osteotomy model, USKECSE(100mg/kg) but not USCSE promoted bone regeneration. In a SD rat postmenopausal osteoporosis model induced by bilateral ovariectomy(OVX), USKECSE through an osteogenic mechanism maintained bone mass, strength, and microarchitecture to the levels of ovary intact rats with no hepatotoxic effect. After a single oral dose(100mg/kg) of USKECSE to adult rats, kaempferol was detectable for 48h, suggesting its significant absorption and distribution in plasma. Peak kaempferol concentration in plasma(Cmax) was 483ng/ml(2M) and at this concentration, kaempferol induced osteoblast differentiation. USKECSE had no genotoxicity and its safety index assessed by preclinical toxicity studies including safety pharmacology was >20-fold. Taken together, we report a novel extraction process that enhanced the osteogenicity and concomitantly reduced hepatotoxicity of tea extract, with significant kaempferol bioavailability, and a favorable systemic safety profile. Based on these data, we propose assessing USKECSE effect for post menopausal osteoporosis treatment.